2014
DOI: 10.1371/journal.pone.0088885
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Changes in Traumatic Symptoms and Daily Life Activity of Children Affected by the 2011 Japan Earthquake and Tsunami over Time

Abstract: BackgroundOn March 11, 2011, Japan was struck by a massive earthquake and tsunami. The tsunami caused tremendous damage and traumatized a number of people, including children. This study aimed to compare traumatic symptoms and daily life activity among children 20 months after the 2011 Great East Japan Earthquake and Tsunami with those observed after 8 months.MethodsThe study comprised two groups. The first comprised 12,524 kindergarten, elementary school, and junior high school children in Ishinomaki City, Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 13 publications
2
22
1
Order By: Relevance
“…Tominaga et al demonstrated the reliability and validity of PTSSC‐15 in Japanese children and adolescents . PTSSC‐15 has been widely utilized at post‐disaster settings in Japan …”
Section: Methodsmentioning
confidence: 99%
“…Tominaga et al demonstrated the reliability and validity of PTSSC‐15 in Japanese children and adolescents . PTSSC‐15 has been widely utilized at post‐disaster settings in Japan …”
Section: Methodsmentioning
confidence: 99%
“…Students of high schools that sustained extensive damage by the tsunami or the earthquake and who used temporary school buildings showed significantly higher levels of depression and anxiety, with significantly lower resilience compared to students of high schools with no damage. 131,133,155 Metabolic Diseases…”
Section: Mental Health Issuesmentioning
confidence: 99%
“…The authors also suggested that the majority of youths with traumatic symptoms resulting from disasters, such as a massive earthquake, may not recover within three years. However, Usami et al (2014b) showed that the baseline PTSSC-15 (a self-completion questionnaire on traumatic symptoms) scores of younger children (kindergarteners and first-to third-grade elementary school students) who participated in the survey 20 months after the Great East Japan Earthquake were significantly lower than those who participated in the survey 8 months after the disaster. Therefore, the psychological symptoms that occur in youth and adolescent survivors may last longer than those that occur in children.…”
Section: Discussionmentioning
confidence: 96%